Entre a intenção e o gesto: A experiência do ProJovem em João Pessoa - Lira, Márcia de Figueirêdo Lucena (2011)
This study aims to analyze the National Program of Social Inclusion of Youngsters: Projovem, in the city of João Pessoa, from 2006 to 2010, having as reference the experience as a coordinator and the reflections of youngsters who participate in the program about facts and processes that took place in their lives. The nature of participation of the youngsters, teachers and managers at Projovem in different localities where the Program was being developed, reveals a commitment to the doing of education and instigates an interest in promoting a public policy for the youth based on the participation of this very youth. The methodological path through qualitative research has been based on the hermeneutic-dialectic, an adequate method for analyzing documents and materials which form the corpus of this study. Its essential elements are: (1) Vídeo Roda de Conversa (chat circle video) with youngsters (2007), talks and trajectories transcribed and analyzed resulting in a new product incorporated to the corpus of this thesis - “About us: youngsters, challenges and perspectives” (2011); (2) Questionnaire (2010) given to 252 youngsters, by the municipal coordination at the Meeting of Leaderships. The analysis of results has revealed six thematic categories: (a) Arrival at the program: different trajectories. (b) For those who have a lot to pursue in life and no time to lose (c) A teacher is not only the one who teaches (d) Seeing the community: contributions for participating as a citizen (e) Professional qualifications: work for whom (f) Conquering fear: perspectives for the future – at this point, youngsters have shown that although the past has not been reassuring and the present brings challenges, a better future may be built. This way, it may be said that although the program (in João Pessoa) has sought the social inclusion of youngsters in its two versions, it still does not manage to meet the needs of the existing demand. Even so, the data reveal the success of the Program in relation to the participating youngsters who successfully finished the Program in this city. In order to resignify the experience lived to the point of inferring the next steps of this policy towards its target audience, it is importance to not only assure the access to such Policy (entrance/enrollment), but also promote permanence and success, given that without learning there is no social inclusion. Other steps are reflexes of the transference of the Program to MEC (Ministry of Education and Culture) as Education Policy and its acknowledgement by the State in its different spheres – Federal, state and municipal, highlighting the importance of Policies for the youth.